Distribution of Naive (CD45R4+) and Memory (CD45RO+) T-Cells in HIV-Infected Puerto Rican Population - Román, Milagros; Rodríguez, José W.; Pagán, Nat O.; Ríos-Olivares, Eddy; Amill, Alejandro; Hunter, Robert (Puerto Rico Health Sciences Journal, 2012)
see manuscript